Optimization of the electrostatic coal adsorption process for sea-salt production from seawater - Ekawati, Yurida; Novareza, Oyong; Setyarini, Putu Hadi; Nugroho, Willy Satrio; Wardana, I Nyoman Gede (Eastern-European Journal of Enterprise Technologies, 2023)
High sulfate content in seawater forms sulfate salts, which become impurities in sea salts. This study investigates the influence of lime juice in the adsorption of sulfate ions in seawater using commercial activated carbon. A full factorial experimental design was employed to optimize the level factors of activated carbon type, adsorbent dosage, and concentration of lime juice in response to the percentage reduction in sulfate concentration. Activated carbon (GCB) and acid-washed activated carbon (GCA) were two types of coconut shells granular activated carbon used for the experiment without further modification. The main effect and interaction effects were analyzed using analysis of variance (ANOVA) and p-values to define the influence of variables affecting sulfate ions adsorption. The adsorption of sulfate ions in seawater was affected by the interaction between the activated carbon type and the dosage, and the concentration of lime juice. The lime juice factor significantly enhanced the performance of activated carbon to adsorb the sulfate ions in seawater, and the factor's contribution was 58.2 %. The optimum sulfate ions reduction from seawater was attained at levels of factors activated carbon GCB, the dosage of 50mg, and the concentration of lime juice 50 µl. The interaction between lime juice and activated carbon pores are electrostatic. The impurities are attracted by the revealed polarity of the activated carbon pores. High electronegativity of lime juice acid pulls the negatively charged ions of the impurities. The more economical activated carbon, GCB, which performed better in sulfate ion adsorption, provides an alternative for reducing sea salt impurities. Hence, GCB can directly be mixed with the seawater to produce high quality sea-salt. Therefore, this study is suitable to improve sea salt product quality that processed with activated carbon